2006
DOI: 10.1063/1.2234317
|View full text |Cite
|
Sign up to set email alerts
|

High-brightness top-emissive polymer light-emitting diodes utilizing organic oxide/Al∕Ag composite cathode

Abstract: This work presents the fabrication of high-brightness (over 30000cd∕m2) top-emissive polymer light-emitting diodes (PLEDs) using a hybrid semitransparent cathode capable of efficient injection of electrons. The composite cathode is comprised of the organic oxide/Al complex as the injection buffer layer covered by a thin Ag overlayer. The anode is made of Ag:Ag2O coated on the glass substrate. The electroluminescence (EL) efficiency of 8.9cd∕A for phenyl-substituted poly(para-phenylene vinylene) copolymer based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Guo et al reported that high performance polymer and small molecule OLEDs with an organic oxide, poly(ethylene glycol) dimethyl ether (PEGDE). Because PEGDE can be evaporated at low temperature compared to other inorganic insulators and improves the device performance as much as the inorganic electron injection layers, it could be a good candidate for an organic electron injection layer [15][16][17]. In this study, the performance of PVK based PLEDs is improved by using PEO/Ca/Al cathode.…”
mentioning
confidence: 84%
“…Guo et al reported that high performance polymer and small molecule OLEDs with an organic oxide, poly(ethylene glycol) dimethyl ether (PEGDE). Because PEGDE can be evaporated at low temperature compared to other inorganic insulators and improves the device performance as much as the inorganic electron injection layers, it could be a good candidate for an organic electron injection layer [15][16][17]. In this study, the performance of PVK based PLEDs is improved by using PEO/Ca/Al cathode.…”
mentioning
confidence: 84%
“…Then, the dividing amplitude is used to calculate the forward emission. The intensity of the forward emission ( , ) from the micro-cavity has been calculated via Equations (1)-(4) [27][28][29][30]: In order to analyze the effect of this micro-cavity in BOLEDs, we implemented a theoretical simulation of its mechanism and found that the transmission of the anode plays an important role in the forward emission. Here, micro-cavity OLEDs can be simplified as a Fabry-Pérot resonator.…”
Section: Optical Properties Of the Micro-cavity In Oledsmentioning
confidence: 99%
“…Then, the dividing amplitude is used to calculate the forward emission. The intensity of the forward emission ( , ) from the micro-cavity has been calculated via Equations (1)-(4) [27][28][29][30]: Assuming I 0 (λ, θ) as the emission of radiating dipoles in the emitting layer, after the wide-angle and multi-beam interferences inside the cavity, the light finally emits through the anode, which is semi-transparent. Then, the dividing amplitude is used to calculate the forward emission.…”
Section: Optical Properties Of the Micro-cavity In Oledsmentioning
confidence: 99%
“…The research was focalised on different topics such as: effect of doping of the organic semiconductor to increase the "transparency" of the energetic barrier to the injection of electron from the contact [6], influence of the trapped and interfacial charges generated in multilayer organic heterostructures on the properties of the device [7], charge tunnelling in multilayer stack and at the interface between organic and anode [8], influence of the thickness and doping of the emission layer on the properties of OLEDs [9], injection of the charge carriers from the electrodes and their migration in correlation with different types of cathodes [10][11][12][13], transport phenomena in organics [14; 15], stacked geometry for efficient double-sided emitting OLED [16], graded mixed layer as active layer to replace heterojunction in OLEDs [17]. The awarding in 2000 of the Nobel prize for researches in the field of conducting polymers has stimulated the development of OLEDs based on polymeric materials, application emphasised years before [18], opening the way of reducing the applied voltages (< 10 V) and increasing the brightness and lifetime.…”
Section: Introductionmentioning
confidence: 99%